Adsorption of water and butanol in silicalite-1 film studied with in situ attenuated total reflectance-Fourier transform infrared spectroscopy - Farzaneh, Amirfarrokh (Langmuir : the ACS journal of surfaces and colloids, 2015)
Biobutanol produced by, e.g., acetone-butanol-ethanol (ABE) fermentation is a promising alternative to petroleum-based chemicals as, e.g., solvent and fuel. Recovery of butanol from dilute fermentation broths by hydrophobic membranes and adsorbents has been identified as a promising route. In this work, the adsorption of water and butanol vapor in a silicalite-1 film was studied using in situ attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy to better understand the adsorption properties of silicalite-1 membranes and adsorbents. Single-component adsorption isotherms were determined in the temperature range of 35-120 °C, and the Langmuir model was successfully fitted to the experimental data. The adsorption of butanol is very favorable compared to that of water. When the silicalite-1 film was exposed to a butanol/water vapor mixture with 15 mol % butanol (which is the vapor composition of an aqueous solution containing 2 wt % butanol, a typical concentration in an ABE fermentation broth, i.e., the composition of the gas obtained from gas stripping of an ABE broth) at 35 °C, the adsorption selectivity toward butanol was as high as 107. These results confirm that silicalite-1 quite selectively adsorbs hydrocarbons from vapor mixtures. To the best of our knowledge, this is the first comprehensive study on the adsorption of water and butanol in silicalite-1 from vapor phase